Anthropogenic disturbance of tropical forests threatens pollination services to açaí palm in the Amazon river delta. Issue 4 (23rd January 2018) - Campbell, Alistair John; Carvalheiro, Luísa Gigante; Maués, Marcia Motta; Jaffé, Rodolfo; Giannini, Tereza Cristina; Freitas, Madson Antonio Benjamin; Coelho, Beatriz Woiski Texeira; Menezes, Cristiano
Abstract: The açaí palm Euterpe oleracea Mart. in the Amazon river delta has seen rapid expansion to meet increased demand for its fruit. This has been achieved by transforming lowland forest habitats (floodplains) into simplified agroforests and intensive plantation in upland areas. As açaí palm makes an important contribution to the economy and food security of local communities, identifying management approaches that support biodiversity and ecosystem processes that underpin fruit production on açaí farms is essential. We compared flower‐visitor communities and açaí fruit production in floodplain forests and upland plantations, across gradients of local management intensity (i.e. açaí density per ha) and surrounding forest cover. The relative contribution of biotic pollination and degree of pollen limitation were assessed using insect exclusion and hand‐pollination experiments. We found that açaí flower visitors are highly diverse ( c . 200 distinct taxa) and had variable responses to disturbance. Bee visitation was higher in floodplains and positively related to surrounding forest cover, but other flower visitors, including specialised curculionid beetles, were unresponsive to changes in surrounding forest cover. However, intensive management practices (i.e. high açaí palm densities) in floodplains and uplands had contrasting effects on flower‐visitor communities, with flower‐visitor richness being lower on intensively managed floodplain farms and ant densities being higher on intensive upland farms. Pollination experiments revealed açaí palm to be highly dependent on biotic pollination. Fruit set in open‐pollinated inflorescences was positively related to flower‐visitor richness and specialised curculionid beetle visitation, whereas the presence of ants on inflorescences had a negative effect. Synthesis and applications . Our study shows that pollinators are essential for açaí fruit production, but that intensive farming practices have eroded the relationship between surrounding forest cover and ecosystem function in floodplains (i.e. conversion of native forest into simplified agroforests) and increased the frequency of antagonistic interactions in uplands (e.g. high ant densities). These findings underline the value of extensive management practices, such as the maintenance of other tree species within farms and adjacent unmanaged forest patches, to ensure the long‐term sustainability of açaí fruit production in the Amazon river delta. Abstract : Our study shows that pollinators are essential for açaí fruit production, but that intensive farming practices have eroded the relationship between surrounding forest cover and ecosystem function in floodplains (i.e. conversion of native forest into simplified agroforests) and increased the frequency of antagonistic interactions in uplands (e.g. high ant densities). These findings underline the value of extensive management practices, such as the maintenance of other tree species within farms and adjacent unmanaged forest patches, to ensure the long‐term sustainability of açaí fruit production in the Amazon river delta.